2008
DOI: 10.1196/annals.1429.008
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Perceptions and Practices around Menarche and Adolescent Menstruation in the United States

Abstract: This overview details the persistence of negative characterizations of the menstrual cycle as a feature of the current cultural context in which girls begin menstrual life in the United States. In addition, research on girls' current menstrual attitudes and experiences within this context are reviewed. Current research suggests that girls are not very knowledgeable about menstruation, and that menstrual education continues to provide girls with mixed messages, such as: menstruation is a normal, natural event, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 62 publications
(166 reference statements)
2
45
0
1
Order By: Relevance
“…The impacts of psychosocial problems with menstruation during adolescence have developmental implications that may continue into adulthood. For example, there is evidence that negative experiences of menarche are associated with menstrual shame and negative body image in adulthood, which in turn can undermine sexual negotiation and lead to sexual risk taking (Schooler, Ward, Merriwether, & Caruthers, 2005;Stubbs, 2008). As Sommer (2009a) points out, girls in resource-poor settings experience the challenges of adjustment to puberty in a social and economic context that makes it hard for them to manage the potentially stigmatizing aspects of menstruation in private.…”
Section: Psychosocial Deprivationsmentioning
confidence: 94%
See 2 more Smart Citations
“…The impacts of psychosocial problems with menstruation during adolescence have developmental implications that may continue into adulthood. For example, there is evidence that negative experiences of menarche are associated with menstrual shame and negative body image in adulthood, which in turn can undermine sexual negotiation and lead to sexual risk taking (Schooler, Ward, Merriwether, & Caruthers, 2005;Stubbs, 2008). As Sommer (2009a) points out, girls in resource-poor settings experience the challenges of adjustment to puberty in a social and economic context that makes it hard for them to manage the potentially stigmatizing aspects of menstruation in private.…”
Section: Psychosocial Deprivationsmentioning
confidence: 94%
“…Researchers have examined preparation and support before and during menarche, girls' experience of menstruation, and positive adjustment to puberty (Chang et al, 2010;Greif & Ulman, 1982;Koff & Rierdan, 1995;McPherson & Korfine, 2004;Ruble & Brooks-Gunn, 1982;Swenson & Havens, 1987). They have also found that emotional support and access to information about puberty can help young people to acquire the knowledge and skills needed for avoiding sexual risk taking (Short & Rosenthal, 2008;Stubbs, 2008). Similar research is very important in contexts where there are taboos against parent-child communication and limited access to information as in many resource-poor settings.…”
Section: Future Researchmentioning
confidence: 94%
See 1 more Smart Citation
“…In Mexico, the cultural stereotype of menstruation is a negative one (Marván & Trujillo, 2010;Marván et al, 2002). In the United States, girls' attitudes and expectations about menstruation are also negatively biased (Stubbs, 2008). Forty percent of women in the United States, as in Western Europe, would stop their period if they could (Aubeny, 2007;Edelman et al, 2007).…”
Section: Views Of Menstruation In the Academic Literaturementioning
confidence: 98%
“…Penelitian menunjukkan bahwa kualitas kedekatan antara orangtua-remaja akan membuat remaja lebih banyak menghabiskan waktu bersama keluarga dan menghabiskan sedikit waktu bersama teman-temannya (Hardway, 2006) Komunikasi antara orangtua-remaja yang baik membantu remaja untuk memperoleh pengetahuan dan keterampilan yang diperlukan untuk menghindari perilaku seksual berisiko (Short, 2008;Stubbs, 2008).…”
Section: Variabelunclassified